RAGE regulates immune cell infiltration and angiogenesis in choroidal neovascularization. - Mei Chen; Josephine V Glenn; Shilpa Dasari; Carmel McVicar; Michael Ward; Liza Colhoun; Michael Quinn; Angelika Bierhaus; Heping Xu; Alan W Stitt (PLoS ONE)
Purpose RAGE regulates pro-inflammatory responses in diverse cells and tissues. This study has investigated if RAGE plays a role in immune cell mobilization and choroidal neovascular pathology that is associated with the neovascular form of age-related macular degeneration (nvAMD). Methods RAGE null (RAGE-/-) mice and age-matched wild type (WT) control mice underwent laser photocoagulation to generate choroidal neovascularization (CNV) lesions which were then analyzed for morphology, S100B immunoreactivity and inflammatory cell infiltration. The chemotactic ability of bone marrow derived macrophages (BMDMs) towards S100B was investigated. Results RAGE expression was significantly increased in the retina during CNV of WT mice (p<0.001). RAGE-/- mice exhibited significantly reduced CNV lesion size when compared to WT controls (p<0.05). S100B mRNA was upregulated in the lasered WT retina but not RAGE-/- retina and S100B immunoreactivity was present within CNV lesions although levels were less when RAGE-/- mice were compared to WT controls. Activated microglia in lesions were considerably less abundant in RAGE-/- mice when compared to WT counterparts (p<0.001). A dose dependent chemotactic migration was observed in BMDMs from WT mice (p<0.05-0.01) but this was not apparent in cells isolated from RAGE-/- mice. Conclusions RAGE-S100B interactions appear to play an important role in CNV lesion formation by regulating pro-inflammatory and angiogenic responses. This study highlights the role of RAGE in inflammation-mediated outer retinal pathology.